Microstructural and geochemical characterisation of mylonites along the Bukit Tinggi fault zone, Peninsular Malaysia / Norsafawati Saaid - Norsafawati , Saaid (2017)
Bukit Tinggi Fault Zone (BTFZ) is a major fault zone in the western flank of Main Range Granite, Peninsular Malaysia. It trends NW-SE with steep dips and a broad zone of granite mylonites occur along the fault zone. This study aims to determine the condition of fault deformation from the microstructures of the mylonites, to determine the sense of shear from mesoscopic and microscopic kinematic indicators, and to determine the chemical changes in the mylonites. The orientation of the foliation and lineation are measured in the field and samples are collected for petrographic and geochemical analyses. Microscopic kinematic studies were done on oriented thin sections. The protolith of the mylonites is a megacrystic biotite granite. Fault deformation has formed fault rocks consisting mainly of protomylonite, minor mesomylonite and rare ultramylonite. The microstructures indicate that quartz and mica behave in a ductile manner during deformation and feldspars are mainly brittle, suggesting that deformation occurred at the brittle-transition zone, which corresponds to about 300°C to 500°C. Kinematic indicators present are S-C foliation, σ-porphyroclast, oblique foliation, mica fish and offset fractured clasts. The BTFZ has oblique slip, with dextral strike-slip component. Mylonites with SW dipping foliation give reverse slip and lesser normal slip is recorded from those with NE dips. The vergence is generally towards the E. For the major elements, there is a slight increase of SiO2 in the mylonites relative to the protolith. The MnO, TiO2, P2O5, MgO, Fe2O3 and CaO are depleted. Na2O, K2O, Cr2O3 and LOI show no clear trend. For the trace elements, Th increased, Sr, Ba, Ga and Zn are depleted, while Nb, Zr, Rb, Y, U and Pb has irregular trends. The chemical changes may be related to silicification and the breakdown of feldspars and biotite during deformation. Late Cretaceous age (84 Ma and 92 Ma) of deformation is obtained from 40Ar/39Ar dating of recrystallized biotite of the mylonite.